Subject Matter Specialists and Organizational Effectiveness of Krishi Vigyan Kendras of Tamil Nadu and Kerala - Bashir, Bimal Puthuparambil; N, Narmatha; K M, Sakhtivel (Journal of Extension Education, 2017)
The study was undertaken with the objective of determining the socio-personal characteristics of Subject Matter Specialists (SMS) of Krishi Vigyan Kendra (KVK) and their relationship with organizational effectiveness. Altogether 65 SMS’ from 12 KVKs across Tamil Nadu and Kerala were selected. The study has concluded that most of respondents were middle aged with more than half of them being female. Majority of them was married, had work experience of below five years and had attended three to five trainings. Most of the respondents had high level of job satisfaction team-work and one-fourth felt a medium to high job stress. More than half of the respondents felt medium level of work load. There was a positive and significant correlation at one per cent level between job satisfaction / team work and organizational effectiveness of KVKs whereas job stress had a negative and significant correlation at five per cent level. Hence it may be concluded that team work, job satisfaction and job stress play a significant role in improving the organizational effectiveness of KVK. More emphasis must be given for team building enhance the job satisfaction level and reduce the job stress among Subject Matter Specialists of KVKs.